VOLUMETRIC PROPERTIES OF CO2-CH4-N2 FLUIDS AT 200°C AND 1000 BARS: A COMPARISON OF EQUATIONS OF STATE AND EXPERIMENTAL DATA - Seitz J.C.; Blencoe J.G.; Joyce D.B.; Bodnar R.J. (My University, 1994)
Predictions of molar volume, excess molar volume, and isochoric P-T trajectories from thirteen published equations of state are compared with one another and with preliminary volumetric data for CO2-CH4-N2 fluids at 200°C and 1000 bars. The equations of state investigated represent a wide variety of empirical and semi-empirical approaches to the modeling of fluids. The experimental data indicate that excess volumes of CO2CH4N2 mixtures are small (<3% of the total volume of the mixture, except near the critical point of CO2). The NIST software package DDMIX yields volumetric properties that are most consistent with our experimental results. Differences in the calculated volumetric properties of mixtures from the different equations of state are significant. For example, estimates of the equilibrium trapping temperature of a fluid inclusion (2000 bars, 60% CO2-20% CH4-20% N2 mixture, V = 59.10 cm3/mol) calculated from various equations of state range from 462–570°C. The major source of error in calculated volumetric properties of fluid mixtures is the inability of equations of state to accurately predict the volumetric properties of the pure components.